Features of the Gestation Course, Delivery, and Postpartum Period in Women with Juvenile Myoclonic Epilepsy - A. V. Yakunina (Неврология, нейропсихиатрия, психосоматика, 2014)
We analyzed 42 pregnancy, delivery, and postpartum period records in women with juvenile myoclonic epilepsy (JME). In most cases, the course of JME was favorable during pregnancy; so administration of subtherapeutic dosages of AEDs in the first and second trimesters of pregnancy can be recommended. Epilepsy decompensation occurred in the postpartum period in 40.5% of cases. Because of a significant risk of epilepsy aggravation during the postpartum period, it is reasonable to increase the dosage of AEDs up to the therapeutic one by the time of expected delivery. We recommend administering AEDs at this dosage for at least three months after the delivery. Neither birth weight or height deviations, nor abnormal Apgar score, nor congenital disorders were revealed in newborns.